Keanekaragaman Serangga Hama pada Tanaman Jagung (Zea mays) di Desa Baringeng, Kabupaten Soppeng, Provinsi Sulawesi Selatan - Phika Ainnadya Hasan; Nurul Hidayah; Nur Fadillah (BIOEDUSCIENCE, 2023)
Background: Baringeng is a corn-producing village in Soppeng Regency, South Sulawesi. The main problem for corn farmers in the town is insect pests. Insect pests damage the plant, which has an impact on decreasing yields. Control of insect pests must be by the type of insect pests. This study aims to calculate the diversity of insect pests of corn in Baringeng Village and the damage they cause. Methods: Data was collected in Takku Hamlet, Baringeng Hamlet, and Tanjonge Hamlet. with a systematic plot sampling method with the help of light traps, sweep nets, and direct collection of pests. Observations included the number of individuals and types of insect pests. Data were analyzed by the Shannon-Wiener diversity index (H'), evenness index (E), dominance index (C), and similarity index. Results: There were three types of insect pests with a total of 153 individuals that attacked corn in Baringeng Village, namely grasshoppers (Oxya sp.), planthoppers (Peregrinus maidis), and armyworm (Spodoptera frugiperda). The diversity index is included in the low category (H'=0.89), the evenness index (E) is in the high sort (E=0.81), the dominance index is in the low sort (C=0.44), and the lowest similarity index shown between Dusun Baringeng and Dusun Takku (IS=50%). Conclusions: The types of insect pests found in Baringeng Village come from three different orders, namely Orthoptera, Lepidoptera, and Hemiptera. Each problem shows other attack characteristics, but all attack the leaves. So that pest control can use natural materials by spraying on leaves, polyculture, crop rotation, or taking pests directly.